Integrated pest Management in cocoa agroforest in Southern Cameroon: constraints and overview - Sonwa, D.J.; Coulibaly, O.; Adesina, A.A.; Weise, Stephan F.; Tchatat, M. (Springer, 2002)
Imports of pesticides have long been subsidised for use in the cocoa agroforests of the humid forest zone of southern Cameroon. With the liberalisation of the cocoa and pesticides sectors and the devaluation of the local currency (CFA franc), farmers are facing fluctuations in the price paid for cocoa and the high cost of farm inputs. Without the support of the extension services, they themselves have developed traditional integrated control methods based on the use of plant extracts mixed with conventional pesticides. From a survey of 300 cocoa farmers, the study assesses the farmers' command of these methods, the pests controlled, the problems encountered and the institutional constraints in the definition and dissemination of integrated control methods. The study concludes with recommendations for research and development towards the better definition and dissemination of integrated control methods